Progress in Hydrogen Production Coupled with Electrochemical Oxidation of Small Molecules. Issue 51 (10th November 2022) - Wang, Tongzhou; Cao, Xuejie; Jiao, Lifang
Abstract: The electrochemical oxidation of small molecules to generate value‐added products has gained enormous interest in recent years because of the advantages of benign operation conditions, high conversion efficiency and selectivity, the absence of external oxidizing agents, and eco‐friendliness. Coupling the electrochemical oxidation of small molecules to replace oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode in an electrolyzer would simultaneously realize the generation of high‐value chemicals or pollutant degradation and the highly efficient production of hydrogen. This Minireview presents an introduction on small‐molecule choice and design strategies of electrocatalysts as well as recent breakthroughs achieved in the highly efficient production of hydrogen. Finally, challenges and future orientations are highlighted. Abstract : Thermodynamically more favorable oxidation reactions of small molecules are widely implemented to replace the oxygen evolution reaction (OER) to achieve the highly efficient production of hydrogen. This Minireview systematically surveys the current progress in electro‐oxidation reactions involving diverse molecules, different electrolytes, and novel mechanisms. The challenges and research directions of this area are highlighted.